iroda ADVANTAGES AND DISADVANTAGES OF TEACHING A FOREIGN LANGUAGE USING THE INTERNET: ADVANTAGES AND DISADVANTAGES OF TEACHING A FOREIGN LANGUAGE USING THE INTERNET - Kamolova, Iroda (Журнал иностранных языков и лингвистики, 2022)
The use of new educational technologies in the learning process is a natural result of modern trends. As already mentioned, there are three models of teaching in higher education: active, passive and interactive. Their application depends on many factors, but in recent years it is the active and interactive models that have become popular. This is partly the result of making high demands on the education process itself. Active methods are characterized by the active work of the students themselves, interactive methods imply even greater activity, as well as the interaction of students with each other and with the teacher.